The Exocyst Complex Subunit EXO70E1-V From Haynaldia villosa Interacts With Wheat Powdery Mildew Resistance Gene CMPG1-V - Zhao, Jia; Zhang, Heng; Zhang, Xu; Wang, Zongkuan; Niu, Ying; Chen, Yiming; Sun, Li; Wang, Haiyan; Wang, Xiue; Xiao, Jin (Frontiers in Plant Science, 2021)
EXO70 belongs to the exocyst complex subunit that plays a critical role in regulating plant cell polarity establishment and defense response. A previous study proved that the E3 ligase CMPG1-V from Haynaldia villosa, a diploid wheat relative, positively regulates the resistance to wheat powdery mildew (Pm), caused by fungus Blumeria graminis f.sp tritici (Bgt). In this study, a member of EXO70 superfamily named EXO70E1-V was isolated from H. villosa, EXO70E1-V interacted with CMPG1-V were shown by Y2H, pull-down, BIFC and LCI assays. It is localized in various subcellular organs, i.e. plasma membrane (PM), endoplasmic reticulum.Co-expression of EXO70E1-V and CMPG1-V showed dot-like structure fluorescence signals were mainly in PM and nucleus. Expression of EXO70E1-V was relatively higher in leaf and was significantly induced by Bgt infection and exogenous application of hormones salicylic acid. Transient or stable over-expression of EXO70E1-V could not enhance/decrease the Pm resistance level, suggesting over-expression of EXO70E1-V alone has no impact on Pm resistance in wheat.